Joint Wear Prediction and Experiments Considering the Influences of Coating and Spherical Joint Clearances - Qian Jing; Baolong Geng (Lubricants)
In recent years, many scholars have carried out a large number of theoretical studies on mechanism systems with joint clearances. Some scholars have conducted relevant experiments with simple planar mechanisms, for example, which have proved the feasibility and applicability of the numerical dynamics calculation method and different contact force models to a certain extent. In order to verify the correctness of the theoretical analysis method of the system dynamics considering coating and joint clearances in the previous stage, this paper independently designed and built the RSSP experimental platform of the spatial four-bar mechanism by taking the shear fork mechanism of the soybean picking and separating machine in farming operations, and measured the dynamic changes in the execution components and the wear depth of the spherical shell surface in different working conditions. The effectiveness of the coating on alleviating vibration, reducing joint wear, and extending the working life of the system mechanism was verified. The experimental conclusions provide strong data support for the subsequent effective and long-life operation of the soybean picking and sorting integrated machine.